Writing academic English - Oshima, Alice (Longman, 1999)
Intermediate-Advanced Level. This best-selling series takes the mystery out of the composition process as it helps college-bound and college-level ESL students quickly improve their ability to write effectively in English. Addressing organization, rhetoric, grammar and mechanics, and sentence structure, these texts offer clear steps, numerous models, and many opportunities for writing practice. This text teaches academic writing skills such as simple outlining, parts of the basic essay, and patterns of organization